2021
DOI: 10.1111/jbi.14140
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of extinction risk in Australian squamate reptiles

Abstract: Species extinction rates are now three orders of magnitude higher than levels recorded for pre-human history (Murray et al., 2014). A central goal of conservation biology is to identify ecological traits that correlate with species extinction risk (Bland, 2017). This area of conservation biology has seen a flurry of growth in the last decade, with global studies conducted on almost all terrestrial vertebrates,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 54 publications
2
22
0
Order By: Relevance
“…These assessment gaps [ 9 , 10 ] led to the use of several automated methods to provisionally assess species [ 11 , 12 ]. These methods employ algorithms including phylogenetic regression models [ 13 15 ], structural equation models [ 16 ], random forests [ 17 , 18 ], deep learning [ 19 , 20 ], Bayesian networks [ 21 , 22 ], and even linguistic analysis of Wikipedia pages [ 23 ]. Most previous attempts (e.g., [ 13 , 17 , 18 ]) employed a binary classification of threatened (categories CR, EN, and VU) versus nonthreatened (NT and LC).…”
Section: Introductionmentioning
confidence: 99%
“…These assessment gaps [ 9 , 10 ] led to the use of several automated methods to provisionally assess species [ 11 , 12 ]. These methods employ algorithms including phylogenetic regression models [ 13 15 ], structural equation models [ 16 ], random forests [ 17 , 18 ], deep learning [ 19 , 20 ], Bayesian networks [ 21 , 22 ], and even linguistic analysis of Wikipedia pages [ 23 ]. Most previous attempts (e.g., [ 13 , 17 , 18 ]) employed a binary classification of threatened (categories CR, EN, and VU) versus nonthreatened (NT and LC).…”
Section: Introductionmentioning
confidence: 99%
“…However, when we excluded range size as a predictor, the R 2 values of all models decreased substantially (Böhm, Williams, et al, 2016). The finding partly reflects the Red List assessment process and also emphasizes that range‐restricted species are generally at a higher risk (Senior et al, 2021). In addition to range size, previous studies suggested that elevational range and population status could be influential to extinction risk and might help to explain variation in extinction risk among small‐ranged species (Meiri & Chapple, 2016).…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, changes in climate (30–60° N/S) can interact with anthropogenic processes, such as habitat loss (e.g., Phrynocephalus golubewii ) and human collecting (e.g., Scincella huanrenensis ), in threatening the extinction of species with small ranges (Whitton et al, 2012). For instance, in Australasia, the positive influence of seasonal precipitation on the threat status of native species is related to enhanced predation and severe modification of habitats in the wetter region (Senior et al, 2021; Tingley et al, 2013). In contrast, we found negative effects of seasonality on the extinction risk of lizards in the Palaearctic and Nearctic, which were also identified by Whitton et al (2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, the distribution of biodiversity loss is driven primarily by climate and anthropogenic sources ( Lu et al 2020 ). Similarly, in Australia extinction risk in reptiles is related to anthropogenic pressures and proximity to human populations as well as climatic variables ( Senior et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%